Salix acmophylla, Tamarix smyrnensis and Phragmites australis as biogeochemical indicators for copper deposits in Elazig, Turkey - Özdemir, Z; Sagiroglu, A (Pergamon-Elsevier Science Ltd, 2000)
The flora of Maden Cayl valley grows in a soil medium which is heavily contaminated with Cu, Fe, Mn, Zn and other metals derived from waste discharges to the Maden Cayl (stream) from the Maden Cu Mining works. Soil, water and plant samples were collected from 47 sites (mostly along the Maden Cayl valley) and analysed for copper. In all the plant species, Cu was concentrated more in the twigs of the plants than in their leaves and flowers. Correlation coefficients (i) were calculated for the correlation between the concentrations of Cu in the twigs of plants and those of the corresponding soil. Statistics of correlation were as follows: Salix acmophylla r = 0.93 (n = 19, P < 0.01), Tamarix smyrnensis r = 0.93 (n = 20, P < 0.01) and Phragmites australis r = 0.72 (n = 18, P < 0.01). Salix acmophylla, Tamarix smyrnensis and Phragmites australis are therefore good indicators of the copper concentrations in the soil and these species could be successfully used for biogeochemical prospecting. These species are typical and common species of the semi-arid Anatolian climate. (C) 2000 Elsevier Science Ltd. All rights reserved.